Assistance In The Use And Utilization Of Posyandu Applications For Monitoring Toddler Growth And Development For Posyandu Cadres In Bulak Village Surabaya City, East Java - Liliek Soetjiatie; Bedjo Utomo; Dyah Titisari (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Human empowerment carried out by Posyandu as a voluntary community organization is very useful, especially in terms of health. Posyandu is managed independently from and for the community as a form of empowerment and provides basic health services for the community. Posyandu is one form of Community-Sourced Health Efforts (UKBM) that is managed from, by, for, and with the community, in order to empower the community and provide convenience to the community in obtaining basic health services. Efforts to improve the role and function of Posyandu are not solely the responsibility of the government, but all components in the community, including cadres. The role of cadres in organizing Posyandu is very large because in addition to being a provider of health information to the community as well as a community mobilizer to come to Posyandu and implement clean and healthy living behavior. Identification of problems that were successfully collected by the Community Service team of Lecturers and Electromedical Engineering Students at Posyandu Bulak Village, which has 15 posyandu, are as follows: 1. Reporting made by posyandu cadres after completion of weighing activities, recording, counseling, etc. is often delayed, even at the end of the new month to provide reports to the Kenjeran Health Center.2. The availability of Posyandu applications that facilitate posyandu cadres both in monitoring the growth of infants and toddlers, planning the next activity, and recording data on infants and toddlers is shorter and in accordance with activities that have been carried out naun has never been utilized by Posyandu cadres. 3. Controlling or monitoring of unhealthy infants cannot be immediately known by the puskesmas. 4.Reporting of Posyandu activities using the F1 Nutrition Form / SKDN is still manual and paper sheets.1. There are several cadres who are elderly, so they need a youth organization assistant to make the report.